RNA processing machineries in Archaea: the 5′-3′ exoribonuclease aRNase J of the β-CASP family is engaged specifically with the helicase ASH-Ski2 and the 3′-5′ exoribonucleolytic RNA exosome machinery. Issue 7 (7th February 2020) - Phung, Duy Khanh; Etienne, Clarisse; Batista, Manon; Langendijk-Genevaux, Petra; Moalic, Yann; Laurent, Sébastien; Liuu, Sophie; Morales, Violette; Jebbar, Mohamed; Fichant, Gwennaele; Bouvier, Marie; Flament, Didier; et al.
Abstract: A network of RNA helicases, endoribonucleases and exoribonucleases regulates the quantity and quality of cellular RNAs. To date, mechanistic studies focussed on bacterial and eukaryal systems due to the challenge of identifying the main drivers of RNA decay and processing in Archaea. Here, our data support that aRNase J, a 5′-3′ exoribonuclease of the β-CASP family conserved in Euryarchaeota, engages specifically with a Ski2-like helicase and the RNA exosome to potentially exert control over RNA surveillance, at the vicinity of the ribosome. Proteomic landscapes and direct protein–protein interaction analyses, strengthened by comprehensive phylogenomic studies demonstrated that aRNase J interplay with ASH-Ski2 and a cap exosome subunit. Finally, Thermococcus barophilus whole-cell extract fractionation experiments provide evidences that an aRNase J/ASH-Ski2 complex might exist in vivo and hint at an association of aRNase J with the ribosome that is emphasised in absence of ASH-Ski2. Whilst aRNase J homologues are found among bacteria, the RNA exosome and the Ski2-like RNA helicase have eukaryotic homologues, underlining the mosaic aspect of archaeal RNA machines. Altogether, these results suggest a fundamental role of β-CASP RNase/helicase complex in archaeal RNA metabolism.